Integrating Local Wisdom into Moral Education: Development of an Akidah Akhlak E-Module - Yumna, Yumna; Hamda, Nurul Majeedah; Asmarita, Desi; Citra, Rini Yulia (International Journal of Islamic Studies Higher Education, 2026)
Akidah Akhlak is an essential component of education, particularly in shaping students' character. However, challenges such as monotonous teaching methods and the lack of engaging digital learning resources reduce students' interest. This study aims to develop and evaluate the effectiveness of a local wisdom-based Akidah Akhlak e-module, using "Gelamai" as a source of inspiration for local cultural values. The e-module teaches commendable and reprehensible moral behavior linked to local cultural values relevant to students' daily lives. The study involved content validation of the e-module by experts, effectiveness measurements through comparisons of pre-test and post-test scores, and practicality evaluations based on feedback from teachers and students. The results indicate that the e-module is highly valid and effective, with significant improvements in students' test scores and positive N-Gain values. Teachers and students found the e-module practical and engaging. These findings demonstrate that a local wisdom-based e-module can enhance students' motivation and understanding of Akidah Akhlak, while contributing to the development of individuals with noble character and social responsibility. The e-module is expected to serve as a more engaging and relevant learning model for students, helping them face global challenges while preserving noble local values.